2020
DOI: 10.1029/2020ja028199
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinally Dependent Low‐Latitude Ionospheric Disturbances Linked to the Antarctic Sudden Stratospheric Warming of September 2019

Abstract: The strongest Southern Hemisphere minor sudden stratospheric warming (SSW) in the last 40 years occurred in September 2019 and resulted in unprecedented weakening of the stratospheric polar vortex. Ionospheric total electron content (TEC) observations are used to provide an overview of statistically significant anomalies in the low‐latitude ionosphere during this event. Quasi‐semidiurnal perturbations of TEC are observed in response to the SSW, similar to those seen during Northern Hemisphere SSWs. Analysis in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 56 publications
2
51
0
Order By: Relevance
“…Nevertheless, the longitudinal variations of the EIA asymmetry induced by PWs have not been discussed. Recently, Goncharenko et al (2020) found that the ionospheric response to this 2019 SSW event exhibit dramatic longitudinal variations, including periodical signals. Their work gives a hint for the explanation of the longitudinal variations of the ionospheric Q6DO found in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the longitudinal variations of the EIA asymmetry induced by PWs have not been discussed. Recently, Goncharenko et al (2020) found that the ionospheric response to this 2019 SSW event exhibit dramatic longitudinal variations, including periodical signals. Their work gives a hint for the explanation of the longitudinal variations of the ionospheric Q6DO found in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…To clearly identify effects of the SSW and separate them from ionospheric variations due to changes in solar cycle, season, and geomagnetic activity, we tested two approaches for the description of background conditions. In the first approach, we followed the methodology originally described in L. P. Goncharenko et al (2020) to develop the "quiet dynamic state" baseline for September low solar activity conditions (L. Goncharenko, 2021). We have also tested an alternative approach through the use of the empirical North America TEC model (Chen et al, 2015).…”
Section: Ionospheric Anomaliesmentioning
confidence: 99%
“…A record strong Antarctic SSW that occurred in September 2019 (Lim et al., 2020; Shen et al., 2020) enables addressing the question of inter‐hemispheric coupling during SSWs with unprecedented detail, as NH middle latitudes have exceptional coverage due to the dense networks of GNSS receivers. Studies of this SSW event demonstrate a record strong quasi 6‐days wave (Q6DW) in the mesosphere‐lower thermosphere (MLT) region and low‐latitude ionosphere (Yamazaki et al., 2020), multiple dynamo processes driving the Q6DW in the ionosphere (Lin et al., 2020), propagation of the Q6DW to 25–30°N in the Asian sector and a strong longitudinal variation in the ionospheric Q6DW at low latitudes (L. P. Goncharenko et al., 2020; Gu et al., 2021; Yamazaki et al., 2020). Other features include a Q10DW in the NH MLT (He et al., 2020), a Q2DW in TEC in the Asian sector at low latitudes, and quasi‐semidiurnal disturbances in TEC at low latitudes (L. P. Goncharenko et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ionospheric responses to SSWs with longer temporal scales such as 2-, 5-to 6-, 10-, or 16-day variations in the F region have also been reported (Goncharenko et al, 2020;Mo et al, 2014;Patra et al, 2014), which are associated with planetary wave (PW) modulations. Quasi-6-day wave (Q6DW) is one of such robust and recurrent oscillations with maximum wind perturbations in the mesosphere and lower thermosphere (MLT), with periods of 5-7 days.…”
Section: Introductionmentioning
confidence: 99%